MT 12S rRNA GENE PCR-RFLP BASED ASSAY FOR MEAT AUTHENTICATION - R, Mayura; Singh, Deepika; Bannalikar, Anil Kumar S (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
For identification and differentiation of meat animal species from known, unknown and adulterated meat samples, the efficacy of mt 12S rRNA gene PCR-RFLP technique on beef, buffalo meat, mutton and chevon was evaluated . All the samples generated 456 bp amplicon on PCR and restriction enzyme digestion of the PCR product with AluI, HhaI, BspTI and ApoI revealed characteristic RFLP patterns. The method was validated by known samples and the species of origin was identified. ApoI and BspTI were useful in differentiation between mutton and chevon. AluI proved to be of value to discriminate between small and large ruminants. Application of this technique on adulterated meat samples of buffalo and cattle meat combinations could detect both animal species down to the level of 20% and 5% with AluI (specific for Cattle) and HhaI (specific for buffalo) respectively. It was possible to differentiate between cattle and buffalo meat samples using AluI enzyme alone.
Keywords: PCR-RFLP; mt 12S rRNA gene; meat adulteration; cattle; buffalo